The truth of the Aleke - Utomi, Moses Ose (The Forever Desert series, 2024)
"Seventeen-year-old Osi is a Junior Peacekeeper in the city, and when the mysterious leader of the Cult, known only as the Aleke, commits a massacre in the capitol and steals the sacred God's Eyes, Osi steps forward to valiantly defend his home"--